2016
DOI: 10.1590/0103-8478cr20151067
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of scientific studies related to pesticide application techniques - air assistance and adjuvant addition

Abstract: The aim of this study was to investigate the effects of air-assisted boom sprayers and addition of adjuvants in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…In previous studies, the Vortex ® system was shown to increase the deposition of a spray mixture inside the canopy of a soybean crop (Baesso et al, 2014), as well as to improve the control of soybean rust, increasing the yield and the mass per thousand soybean grains (Christovam et al, 2010;Prado et al, 2010). On the other hand, cases have been reported wherein such assisted methods did not influence spray deposition levels (Aguiar Júnior et al, 2011), and in some studies, air-assisted boom spraying had no effect on the performance of agrochemicals, in that it did not potentiate nor did it compromise the control levels of phytopathogenic fungi (Oliveira et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the Vortex ® system was shown to increase the deposition of a spray mixture inside the canopy of a soybean crop (Baesso et al, 2014), as well as to improve the control of soybean rust, increasing the yield and the mass per thousand soybean grains (Christovam et al, 2010;Prado et al, 2010). On the other hand, cases have been reported wherein such assisted methods did not influence spray deposition levels (Aguiar Júnior et al, 2011), and in some studies, air-assisted boom spraying had no effect on the performance of agrochemicals, in that it did not potentiate nor did it compromise the control levels of phytopathogenic fungi (Oliveira et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Besides using assisted boom sprayer systems, the deposition and coverage of the leaf surface by sprayed chemicals can be maximized by adjusting other factors, such as: the spectrum of the droplets (Silva et al, 2014, Weber et al, 2017França et al, 2018), spray pressure (Cunha et al, 2016), spray nozzle type (Cunha et al, 2014;Madureira et al, 2015;Cunha et al, 2016, Durão & Boller, 2017, adding adjuvants to the spray (Cunha et al, 2014;Madureira et al, 2015;Oliveira et al, 2016), and changing the volume of the mixture (Cunha et al, 2014;Prado et al, 2015;Weber et al, 2017;Roehrig et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing the effect of the air supply through a series of works, Oliveira et al (2016) indicated that this mechanism of support to the spray bar had no effect on the performance of agrochemicals and the control levels of phytopathogenic fungi. The contrasting and variable effects on the Vortex ® system may be associated with the different canopy opening levels, which can be influenced by the plant arrangement (Holtz et al, 2014), depending on the characteristic of the cultivar Tormen et al, 2012), as well as by the time of the day of spraying, due to the variation of the horizontal angle of soybean leaves throughout the day (Graziano et al, 2017;Moura et al, 2017).…”
Section: Resultsmentioning
confidence: 99%